Application of extreme value analysis in the assessment of budget variance risk - Kes, Zdzisław; Kuźmiński, Łukasz (Probabilistyczna analiza wartości ekstremalnych w ocenie ryzyka wystąpienia odchyleń budżetowych, 2019)
This paper presents the methods for the evaluation of budget variance risk, i.e. the risk of a difference between the budgeted and actual figures. The postulated approach is based on extreme value analysis (EVA), to offer, among other things, the evaluation of maxima distribution parameters for studied phenomena. The proper recognition of these parameters yields potential for calculation of probabilities for budget variance to pass certain levels established as critical. This methodology can be used to evaluate deviation levels by time period, and to compare them against historical data. The main objective of this paper was to examine the utility of the theory of extreme values in the estimation of budget deviation risks. The study presents the results of probabilistic analyses of data obtained from a budgetary cost control unit of a production company located in eastern Poland, for the period of 2011-2012. The developed method of analysis and assessment of budget deviations is in line with the development of concepts and methods of management accounting
Econometrics = Ekonometria, 2019, Vol. 23, No. 2, s. 80-98
Keywords: budgetary control; statistical methods of budgetary control; extreme value analysis; kontrola budżetowa; statystyczne metody kontroli budżetowej; analiza wartości ekstremalnych